Study of Forced Marriage as a Form of Sexual Violence - Itok Dwi Kurniawan (UNES Law Review, 2023)
The implementation of forced marriages as a social problem has turned into a legal problem. In its development, forced marriage has become a form of criminal sexual violence as regulated in Law Number 12 of 2022 concerning Criminal Sexual Violence. This article will analyze forced marriage as a type of criminal act of sexual violence. The focus of the study is related to the definition of the criminal act of forced marriage and the form of criminal responsibility for perpetrators of the criminal act of forced marriage. The results of this research are that the criminal act of forced marriage is a violation of human rights and is a form of criminal sexual violence.